Graphene nanosheets, carbon nanotubes, graphite, and activated carbon as anode materials for sodium-ion batteries1. Issue 19 (21st May 2015) - Luo, Xu-Feng; Yang, Cheng-Hsien; Peng, You-Yu; Pu, Nen-Wen; Ger, Ming-Der; Hsieh, Chien-Te; Chang, Jeng-Kuei
<x xml:space="preserve">Abstract</x> The graphene nanosheet electrode with excellent high-rate performance and satisfactory cyclability is an ideal anode for sodium-ion batteries.